Meningkatkan Aktivitas dan kemampuan Literasi (Baca) Menggunakan Teknik Bermain pada Siswa Kelas III SDN 1 Sawah Lama Bandar Lampung TP 2019/2020 - Titawati, Titawati (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
The purpose of the study is in line with the formulation of the problem, so this study aims to increase literacy learning activities and outcomes using Playing Techniques for Class III students of SD Negeri 1 Sawah Lama Bandar Lampung in the 2019/2020 school year. The method used is CAR with planning, implementation, observation and reflection steps carried out in 3 cycles. The research subjects were the third grade students of SD Negeri 1 Sawah Lama Bandar Lampung totaling 34 students. The results showed that the application of playing techniques could increase the activity of learning Indonesian language literacy materials for Class III students of SD Negeri 1 Sawah Lama Bandar Lampung for the 2019/2020 school year.